Genetic and biomarker modulation of arterial stiffness change in the SardiNIA population cohort - Asefa, Nigus G.; Meirelles, Osorio; Lakatta, Edward; Fiorillo, Edoardo; Scuteri, Angelo; Cucca, Francesco; Marongiu, Michele; Delitala, Alessandro; Schlessinger, David; Launer, Lenore J. (Frontiers in Epidemiology, 2024)
Background and aims: Arterial stiffness (AS), quantified by pulse wave velocity (PWV), arises due to impaired arterial elastic tissue and smooth muscle dysfunction. We aimed to examine the longitudinal association of genetic, lipid and inflammation biomarkers with PWV and how these associations may change with aging.We utilized genotype and four time-point biomarker data from the SardiNIA cohort (n = 6,301; mean baseline age 43.3 [SD 17.3]; 58% females). To investigate the association of PWV with genetic variants, lipid, and inflammation biomarkers, we employed linear mixed modeling, using age as the time scale. Biomarkers exhibiting significant longitudinal associations were categorized into tertiles and individuals within the second tertile or those with heterozygous alleles were excluded, leaving a cohort of 2,000 individuals. This cohort was further divided into four risk groups: low genetic and low biomarker (L-L), low genetic and high biomarker (L-H), high genetic and low biomarker (H-L), and high genetic and high biomarker risk (H-H). Subsequent analyses focused on these risk groups to assess their association to PWV with time.Results: Using the complete dataset, we found a significant longitudinal association of total cholesterol (TC), triglycerides (TG), fibrinogen (FGN), and total white blood cell count (TWBC) with PWV, all with p < 3.33X10 -3 . After grouping, individuals with homogeneous risk alleles of SNP rs3742207 and high baseline TG levels (H-H group) exhibited a 1.39-fold higher PWV (m/s) (95% CI, 1.17-1.64, p=1.21 X 10 -4 ) compared to the L-L group. Similarly, individuals in the H-H group of rs3742207-TWBC combination showed 1.75 times higher PWV (95% CI, 1.48-0.2.07, p=1.01 X 10 -10 ) compared to the L-L group. Similar patterns were observed for groups based on SNP rs7152623-TWBC risk. Furthermore, these associations became more pronounced with increasing age (p < 3.33 X 10 -3 ).The longitudinal association of TG and TWBC biomarkers with PWV varied by SNPs rs3742207 and rs7152623 genotype. Further studies are warranted to investigate the function of genetics, lipids, and inflammation biomarkers on PWV change.